2014
DOI: 10.7567/jjap.53.03db01
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between center-peaked plasma density profiles and harmonic electromagnetic waves in very high frequency capacitively coupled plasma reactors

Abstract: An understanding of the factors that control radial plasma uniformity in very high frequency (VHF) capacitively coupled plasma (CCP) sources is important for many plasma processes in semiconductor device manufacturing. Here, we report experimental measurements and high-resolution self-consistent numerical simulations that illustrate the plasma density profile and the higher harmonic wave content in two types of VHF-CCP testbench reactors. A distinct sharp center peak superimposed on a broad center peak in argo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 25 publications
1
41
1
Order By: Relevance
“…Miller et al [24] and Lane et al [25] showed experimentally the existence of harmonic excitations. A correlation between the presence of higher harmonics and center-peaked plasma density profiles was demonstrated by Sawada et al [26]. However, the mechanisms causing these harmonic excitations were not clarified.…”
mentioning
confidence: 95%
“…Miller et al [24] and Lane et al [25] showed experimentally the existence of harmonic excitations. A correlation between the presence of higher harmonics and center-peaked plasma density profiles was demonstrated by Sawada et al [26]. However, the mechanisms causing these harmonic excitations were not clarified.…”
mentioning
confidence: 95%
“…The important role of the higher harmonics in affecting the plasma nonuniformities was emphasized by Upadhyay et al [153] and Sawada et al [154] By a combination of experimental measurements and high-resolution, self-consistent 2D fluid simulations, the authors concluded that the presence of higher harmonics is strongly correlated with the occurrence of the sharp central peak of the plasma density. Miller et al [155] observed distinct differences in the spatial distributions and harmonic content of RF fields in the plasma at the different frequencies (13.56 MHz,60 MHz,and 176 MHz).…”
Section: Nonlinear Standing Wave Excitationmentioning
confidence: 98%
“…However, analyzing the standing wave effects at the fundamental excitation frequency does not explain the observation of a sharp center-peaked profile in semiconductor processing reactors with wafer radius of $10 cm driven at 60 MHz. 32 For this purpose, a high-resolution fluid model coupled with plasma-EM wave governing equations was developed by Upadhyay et al 32,33 The computational meshes (in space and time) were very small, providing adequate spatiotemporal resolution to resolve the higher harmonic EM wave contents and to investigate the effect of the higher harmonics of the EM field on the plasma density radial profiles. The calculated spatial profile of the plasma density showed a qualitative agreement with the experimental observation of a sharp center-peaked electron density profile, and especially, the frequency spectrum of the axial electric field obtained from its fast Fourier transform, is very likely a reproduction of the phenomena experimentally observed by Miller et al 34 The sharp center-peaked profile is believed to be highly correlated with the higher harmonics, as is shown in Fig.…”
Section: B Numerical Simulationsmentioning
confidence: 99%